Delirio di immobilità. Gli Stati di grazia di Davide Orecchio (TEST Ticontre. Theory Text Translation, 2018)
The analysis proposes a thematic approach to the novel Stati di grazia by Davide Orecchio. The text focuses on the life of some men and women who tried to fight the Argentinian dictatorship in the Seventies. The result of the struggle has been fatal and tragic for many of them, whereas the ones who survived have taken the road of a melancholy exile. Some interpretative instruments derived by Freud and Benjamin, connected to the reflection on trauma and to the character of ‘brooder’, allow to delineate the victim-focused paradigm. This paradigm is based on a series of missed actions and on the absence of action, substituted by an existential static and inactive grey zone. The pain of defeat, the intrusiveness and the weight of memory, the perpetual memory, the compensatory tendency to telling and listening stories, the regressive desire of being looked after are the elements which articulate the story. Metaphor of this melancholic and centripetal universe is a linguistic aspect typical of the characters of the novel, the list of things, objects and situations, nothing but a behaviour close toward the future which represents the file of lost occasions and of difficulties of the present.L’analisi propone un approccio tematico al romanzo Stati di grazia di Davide Orecchio. Il testo si focalizza sulla vita di alcuni uomini e donne che hanno cercato di opporsi alla dittatura argentina degli anni Settanta. L’esito della lotta è stato per molti di loro drammatico e tragico; per chi invece è sopravvissuto si è aperta la strada di un malinconico esilio. Alcune griglie interpretative derivate da Freud e Benjamin, legate alla riflessione sul trauma e alla figura del ‘rimuginatore’, consentono di delineare un paradigma vittimario che si esplica in una fenomenologia dell’atto mancato e nel blocco dell’agency, sostituita da una zona grigia esistenziale statica e inerte. A scandire il romanzo sono così il dolore della sconfitta, l’invadenza e il peso della memoria, la tendenza compensatoria al racconto e all’ascolto, il desiderio regressivo di accudimento. Metafora di questo universo malinconico e centripeto diviene un atto linguistico tipico dei personaggi del testo, cioè l’elenco di cose, oggetti e situazioni, una pratica residuale che ha perso intenzionalità attiva e rappresenta ormai solo l’archivio delle occasioni perse e delle difficoltà del presente.